Investigando os mecanismos de síntese de ácidos graxos insaturados em Aspergillus fumigatus: insights funcionais sobre a delta 9 desaturase SdeA - Yanes-Filho, Gilberto (Universidade Federal de São Carlos, 2025)
Invasive fungal infections caused by Aspergillus fumigatus pose a significant clinical challenge, particularly due to the limited antifungal therapies available and the central role of essential metabolic pathways in pathogen survival. Among these pathways, unsaturated fatty acid metabolism is especially importante and the gene encoding a delta 9 fatty acid desaturase (sdeA) is responsible for the production of unsaturated fatty acids oleic acid (C18:1) and palmitoleic acid (C16:1). The absence or reduced expression of sdeA renders the fungus dependent on an exogenous supply of these fatty acids, highlighting its potential as an antifungal target. In this study, the functional and structural importance of SdeA was investigated through the generation of conditional mutants, deletions of the Cytb5 and hinge domains, site-directed mutations in catalytic residues, and complemented strains integrated at a safe-harbor locus using CRISPR–Cas9. The analyses included genotypic validation, subcellular localization studies, phenotypic assays under different nutritional conditions, and virulence testing in an invertebrate model. The results demonstrated that sdeA is essential in A. fumigatus and that the encoded protein functions as a dimeric desaturase with a structural organization that optimizes electron transfer, differing from the mechanism observed in mammalian desaturases. Deletion of the Cytb5 domain did not alter the perinuclear and reticular subcellular localization of the protein; however, multiple lines of evidence indicate that its modification compromises fungal viability, with partial growth recovery observed in the presence of oleic acid. In silico structural modeling was instrumental in guiding the understanding of SdeA role in lipid metabolism, environmental stress adaptation, and A. fumigatus virulence.
Investigating the mechanisms of unsaturated fatty acid synthesis in Aspergillus fumigatus: functional insights into the delta 9 desaturase SdeA
Keywords: Aspergillus fumigatus; delta 9 desaturase; metabolismo lipídico; CRISPR-Cas9; mutantes condicionais; delta 9 desaturase; condiional mutants; SdeA; CIENCIAS BIOLOGICAS::GENETICA::GENETICA MOLECULAR E DE MICROORGANISMOS; 3. Saúde e Bem-Estar